Affixation Errors and Contextual Meaning Alignment in Undergraduate Theses - Syahriandi Syahriandi; Radhiah; Reza Pahlevi Ginting; Masithah Mahsa (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
This study examines affixation errors in student theses, emphasizing not only the accuracy of the affix form but also the suitability of grammatical meaning with contextual meaning. This study uses a qualitative descriptive design with data sources in the form of ten theses of students of the Indonesian Language Education Study Program, Malikussaleh University. Data were collected through reading and note-taking techniques and classified into three categories: affixation rule errors, grammatical function and meaning inaccuracies, and root word determination inaccuracies. The results of the study found 19 error data, consisting of eight affixation rule errors, nine function and meaning errors, and two root word determination errors. The most dominant error was the mismatch of the affixed form with the contextual meaning of the sentence, especially in the use of -kan, -an, and the formation of verbs and nouns. The novelty of this study lies in the integrated analysis of morphophonemic rules, root word standardization, and contextual semantics. This study contributes to the development of a diagnostic framework for affixation errors and the strengthening of Indonesian academic writing learning. Penelitian ini mengkaji kesalahan afiksasi dalam skripsi mahasiswa dengan menitikberatkan tidak hanya pada ketepatan bentuk afiks, tetapi juga pada kesesuaian makna gramatikal dengan makna kontekstual. Penelitian ini menggunakan desain deskriptif kualitatif dengan sumber data berupa sepuluh skripsi mahasiswa Program Studi Pendidikan Bahasa Indonesia Universitas Malikussaleh. Data dikumpulkan melalui teknik baca-catat dan diklasifikasikan ke dalam tiga kategori, yaitu kesalahan kaidah afiksasi, ketidaktepatan fungsi dan makna gramatikal, serta ketidaktepatan penentuan kata dasar. Hasil penelitian menemukan 19 data kesalahan, terdiri atas delapan kesalahan kaidah afiksasi, sembilan kesalahan fungsi dan makna, serta dua kesalahan penentuan kata dasar. Kesalahan paling dominan terdapat pada ketidaksesuaian bentuk berafiks dengan makna kontekstual kalimat, khususnya pada penggunaan -kan, -an, serta pembentukan verba dan nomina. Kebaruan penelitian ini terletak pada analisis terpadu antara kaidah morfofonemik, standardisasi kata dasar, dan semantik kontekstual. Penelitian ini berkontribusi dalam penyusunan kerangka diagnostik kesalahan afiksasi serta penguatan pembelajaran penulisan akademik bahasa Indonesia.